2020
DOI: 10.1016/j.heliyon.2020.e03919
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor treatment of female mice that express APOE4 at an age of advanced pathology mitigates behavioral and cerebrovascular dysfunction

Abstract: APOE4 is a major genetic risk factor for Alzheimer's disease and high amyloid-β (Aβ) levels in the brain are a pathological hallmark of the disease. However, the contribution of specific APOE-modulated Aβ-dependent and Aβ-independent functions to cognitive decline remain unclear. Increasing evidence supports a role of APOE in modulating cerebrovascular function, however whether ameliorating this dysfunction can improve behavioral function is still under debate. We have previously demonstrated that systemic epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…Therefore, E4FAD− and E4FAD+ mice were utilized to test whether candesartan modulates functions specific to the interaction of Aβ and APOE4 or were generally applicable to APOE4 . Previous research in E4FAD− and E4FAD+ mice has demonstrated that alterations in behavior and neuronal protein levels occurs earlier in female mice (∼6 months) than in male mice (∼8 months) ( Wolf et al, 2013 ; Thomas et al, 2016 , 2017 ; Tai et al, 2017 ; Zaldua et al, 2020 ). Therefore, candesartan treatments were initiated at different ages for female and male E4FAD mice to try and broadly match AD-relevant pathology at the start of treatment.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, E4FAD− and E4FAD+ mice were utilized to test whether candesartan modulates functions specific to the interaction of Aβ and APOE4 or were generally applicable to APOE4 . Previous research in E4FAD− and E4FAD+ mice has demonstrated that alterations in behavior and neuronal protein levels occurs earlier in female mice (∼6 months) than in male mice (∼8 months) ( Wolf et al, 2013 ; Thomas et al, 2016 , 2017 ; Tai et al, 2017 ; Zaldua et al, 2020 ). Therefore, candesartan treatments were initiated at different ages for female and male E4FAD mice to try and broadly match AD-relevant pathology at the start of treatment.…”
Section: Resultsmentioning
confidence: 96%
“…Further, although the AT1 receptor is expressed on brain endothelial cells and excessive AT1 receptor signaling has been shown to directly impair endothelial cell function ( Fleegal-DeMotta et al, 2009 ), in our study candesartan treatment did not result in changes to vascular permeability (fibrinogen) in female E4FAD− and E4FAD+ mice. Therefore, blood-brain barrier dysfunction may be too far advanced in E4FAD mice at the ages evaluated in this study ( Thomas et al, 2016 , 2017 ; Zaldua et al, 2020 ) for candesartan to have exerted a beneficial effect, or the contribution of the AT1 receptor to cerebrovascular dysfunction is minimal in E4FAD mice. For either event, the result may be that a disrupted blood-brain barrier in E4FAD mice enabled candesartan to cross into the brain.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations